Emerging organic contaminants in sludges : analysis, fate and biological treatment - Caminal, Gloria; Eljarrat, Ethel; Barcelo, Damia; Vicent, Teresa (The Handbook of Environmental Chemistry, 2013)
There are a growing number of new chemicals in the environment that represent an ascertained or potential risk. Many of them can be found in sewage sludge and are the subject of this volume. Experts in the field highlight their occurrence and fate, risks of biosolid use, advanced chemical analysis methods, and degradation techniques with a special focus on biodegradation using fungi. In the final chapter conclusions and trends are offered as a point of departure for future studies. The double-disciplinary approach combining environmental analysis and engineering makes the book a valuable and comprehensive source of information for a broad audience, such as environmental chemists and engineers, biotechnologists, ecotoxicologists and professionals responsible for waste and water management.